From swamp to city-- ! : 1863-1963 : the story of Dalby : city of wheatsheaves and gateway to Queensland oil. - Wade, G. H.; Dalby (Qld.). Council ([Dalby, Qld. : Council of the Town of Dalby, 1963)
Inset article on page 6, "Early troubles with blacks" outlines Aboriginal resistance, led by the "Muckadilla tribe", to European settlement and its eventual subduing. Scattered references to Aboriginal people elsewhere.
"Compiled and designed by G.H. Wade ... for the Council of the town of Dalby"--P. [1].
Cover title.
Keywords: Race relations - Violent - Massacres, murders, poisonings etc. - To 1900.; Economic sectors - Agriculture and horticulture - Grain; Settlement and contacts - Colonisation - 1851-; Economic sectors - Agriculture and horticulture - Cotton; Mandandanji people (D44) (Qld SG55-16); Dalby (Qld.) -- History; Dalby (SE Qld SG56-13)